2022
DOI: 10.1287/opre.2021.2142
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note—Capacitated Assortment Optimization: Hardness and Approximation

Abstract: Assortment optimization is an important problem arising in various applications. In many practical settings, the assortment is subject to a capacity constraint. In “Capacitated Assortment Optimization: Hardness and Approximation,” Désir, Goyal, and Zhang study the capacitated assortment optimization problem. The authors first show that adding a general capacity constraint makes the problem NP-hard even for the simple multinomial logit model. They also show that under the mixture of multinomial logit model, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Finally, discrete choice models have been a fundamental building block in many research topics in revenue management Fisher 2007, Bernstein et al 2015), and it continues to be an active area of research. In particular, the assortment optimization problem was addressed under the LC-MNL model (Méndez-Díaz et al 2014, Rusmevichientong et al 2014, Désir et al 2022,…”
Section: Overview Of the Discrete Choice Modelsmentioning
confidence: 99%
“…Finally, discrete choice models have been a fundamental building block in many research topics in revenue management Fisher 2007, Bernstein et al 2015), and it continues to be an active area of research. In particular, the assortment optimization problem was addressed under the LC-MNL model (Méndez-Díaz et al 2014, Rusmevichientong et al 2014, Désir et al 2022,…”
Section: Overview Of the Discrete Choice Modelsmentioning
confidence: 99%
“…Since all RUM can be approximated by the LC-MNL our results imply that over that class of discrete choice models, the bound R ≤ mR * is arbitrarily close for all m ≤ n. Since the MNL is a regular model, the bound for the previous section applies, so we conclude that for all RUMs, the bound R ≤ min(m, n)R * is arbitrarily close. It is worth to mention that similarly to the TAOP, the RAOP under the LC-MNL is NP-hard [Désir et al, 2020] 1 .…”
Section: Bounds For Models That Satisfy the Monotone Utility Propertymentioning
confidence: 99%
“…In their study of the TAOP under the LC-MNL,Désir et al [2020] considered its continuous relaxation and showed that there is no efficient algorithm that can achieve an approximation factor guarantee of at least O( 1 m 1−δ ) for any constant δ > 0 unless N P ⊂ BP P .…”
mentioning
confidence: 99%
“…v k ′ j µ LR (j, S * )p j using bounds from ( 5) and (7). We have where δ 2 := ǫα max i∈[n] { h, u i }.…”
Section: Fptas For the Generalized Markov Chain Model With Low Rank M...mentioning
confidence: 99%
“…+ α p = 1), and v k ∈ Q n + for all k ∈ [p] denote the MNL parameters for segment k. However, even for a mixture of MNL model with two segments, Rusmevichientong et al [17] show that the assortment optimization problem is NP-hard. Moreover, Désir et al [7] show that it is hard to approximate within a factor better than Ω(n 1−ǫ ) in general. So the mixture of MNL model is quite intractable.…”
Section: Introductionmentioning
confidence: 99%